“BELT AND ROAD INITIATIVE” AND THE NEW CONFIGURATION OF KAZAKHSTAN-CHINESE RELATIONS (Journal of Oriental Studies, 2023)
The topic of the study covers Kazakh-Chinese relations over the past 30 years, namely the transformation of their situation as a result of China’s proclamation of the Belt and Road Initiative (BRI) in 2013.The purpose of the article is to analyze and periodize Kazakh-Chinese relations in the context of the most significant areas of cooperation in its different stages, as well as taking into account the influence of the political and economic agenda of the two countries.The article argues that the BRI was a turning point in the formation of the current structure of interstate relations between Kazakhstan and China.The work has practical significance for researchers in the field of Chinese studies, international relations, and political science.The study structures and summarizes publicly available information on Kazakh-Chinese joint ventures involved in non-resource sectors of the economy in the Republic of Kazakhstan.The methodology of the article is structured as follows: a literature review of scientific publications on the research topic was conducted.In particular, an analysis is provided of the works of Chinese authors, who often apply pro-state concepts for the theoretical substantiation of bilateral relations, as well as English-language authors who measure the BRI through the prism of a critical understanding of China’s geo-economic strategy.The article builds a periodization according to the stages of relations between Kazakhstan and China in the context of changes in the structure of political and economic relations.This article is an attempt to analyze and periodize three decades of Kazakh-Chinese relations, which is a contribution to the national scientific literature on a given topic.Key words: Kazakhstan, China, bilateral relations, Belt and Road Initiative.